2020
DOI: 10.1101/2020.04.03.003632
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-Canonical Targets of HIF1a Drive Cell-Type-Specific Dysfunction

Abstract: 15All mammalian cells sense and respond to insufficient oxygen, or hypoxia, through the activity of 16 hypoxia-inducible factors (HIFs), an evolutionarily conserved family of transcriptional regulators 17 that promote oxygen-independent energy metabolism and angiogenesis. While HIF activation is 18

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 84 publications
(106 reference statements)
2
0
0
Order By: Relevance
“…The embryonic vasculature is subsequently remodeled at neonatal stages by neuronal and glial populations (Bozoyan et al, 2012;Harb et al, 2013;Ma et al, 2013;Paredes et al, 2018;Segarra et al, 2018;Vasudevan et al, 2008), including NG2 glia (Minocha et al, 2015). Several studies show that OPC-encoded HIF function regulates cellautonomous OPC maturation and myelination as well as WM angiogenesis via paracrine signaling (Allan et al, 2020;Yuen et al, 2014;Zhang et al, 2020). Here, we extend insights into this process and show the OPCs and BVs engage in further cell-cell interactions in the neonatal brain.…”
Section: Discussionsupporting
confidence: 52%
“…The embryonic vasculature is subsequently remodeled at neonatal stages by neuronal and glial populations (Bozoyan et al, 2012;Harb et al, 2013;Ma et al, 2013;Paredes et al, 2018;Segarra et al, 2018;Vasudevan et al, 2008), including NG2 glia (Minocha et al, 2015). Several studies show that OPC-encoded HIF function regulates cellautonomous OPC maturation and myelination as well as WM angiogenesis via paracrine signaling (Allan et al, 2020;Yuen et al, 2014;Zhang et al, 2020). Here, we extend insights into this process and show the OPCs and BVs engage in further cell-cell interactions in the neonatal brain.…”
Section: Discussionsupporting
confidence: 52%
“…A recent publication has demonstrated that chronic HIF-1a accumulation in pluripotent stem cell-derived oligodendrocyte progenitors blocked differentiation. Inhibition of HIF-1 signaling restored oligodendrocyte formation even in partially hypoxic human oligocortical spheroids (62). Both observations fit well with the theory that demyelinated axons that are electrically intact with properly firing neurons provide an increased likelihood for remyelination [reviewed in (63,64)].…”
Section: Discussionsupporting
confidence: 77%